GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 13771712 species occurrences available in GBIF matching the query: TaxonKey: Actinopterygii. The dataset includes 13771712 records from 1105 constituent datasets: 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 712 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 1 records from Naturalis Biodiversity Center (NL) - Crustacea. 2 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 288 records from National Biodiversity Data Bank. Observation records, 1900-2014. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 1034 records from University of Ghent - Zoology Museum - Vertebratacollectie. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 94 records from Plan de vertebrados de la Patagonia. 2 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 468354 records from Royal Dutch Angling Association (SVN) - Piscaria. 24 records from A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae).. 1949 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 308 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 27 records from Redescription of Apteronotus mariae (Eigenmann & Fisher, 1914) and the taxonomic status of Apteronotus jurubidae (Fowler, 1944) (Gymnotiformes: Apteronotidae).. 549 records from OEH Atlas of NSW Wildlife. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 391 records from CSUC Vertebrate Collection. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 9 records from A new species of the genus Aphanius (Nardo, 1832) (Actinopterygii, Cyprinodontidae) from Algeria.. 20 records from Truchas Mexicanas. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 252 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 14 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 379 records from WNMU Fish Collection (Arctos). 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 4793 records from Marine species distributions in Irish coastal waters. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 2488 records from Colección de peces dulceacuícolas de Costa Rica. 17 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 60668 records from ecoscope_observation_database. 1642 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 86 records from Coastal and marine species. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 690 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 2 records from A new phreatic catfish of the genus Phreatobius Goeldi 1905 from groundwaters of the Itenez River, Bolivia (Siluriformes: Heptapteridae).. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 1 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 26 records from Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile.. 483 records from National Taiwan Ocean University. 3170 records from Zoology (Museum of Evolution - Uppsala). 1 records from PlutoF platform observations. 10 records from TCWC Marine Invertebrates. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 8 records from PReCAST Marine Mammal Sightings. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 27366 records from CSIRO Ichthyology provider for OZCAM. 239 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 708423 records from Fishbase. 190 records from Irish Federation of Sea Anglers Catch Data. 418 records from EPA River Biologists data. 113064 records from Occurrence records of southern African aquatic biodiversity. 172 records from Paläontologie Marburg. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 145954 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 260 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 345 records from Collection du Musée d'Histoire Naturelle de Nice. 168725 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 8 records from New species of the catfish genus Trichomycterus (Siluriformes, Trichomycteridae) from the headwaters of the rio São Francisco basin, Brazil.. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 2 records from Apistogramma eremnopyge, a new species of cichlid fish (Teleostei: Cichlidae) from Peru.. 498 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 21 records from NPL collections. 5 records from Local BioBlitz Challenge 2013. 3032 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 9855 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 97 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 189 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 32840 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 17477 records from Inventario Español de Especies Terrestres (MAGRAMA). 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 1004 records from National Museum of Marine Biology and Aquarium. 49847 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 41 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 5736 records from UAFMC Fish. 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 67798 records from NCSM Fishes Collection. 239 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 2 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 104 records from AM: Freshwater Invertebrates (1900-2005). 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 303 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 430 records from BioFokus. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 2558 records from Merseyside BioBank - North Merseyside Fish (unverified). 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 9757 records from UAM Fish Collection (Arctos). 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 127 records from Clare Biological Records Centre dataset. 680 records from The Fish Collection at the Zoologische Staatssammlung München. 16769 records from University of Florida Vertebrate Paleontology. 169 records from Bioblitz 2013 Copenhagen Denmark. 1193 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 8 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 1 records from CUMV Mammal Collection (Arctos). 1918 records from ISM Ichthyology Collection. 89246 records from CUMV Fish Collection (Arctos). 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 347 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 904 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 7 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 91 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 20621 records from Artdata. 10 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 1 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 28572 records from Museum Victoria provider for OZCAM. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 314 records from Peces laguna El Tinije. 51426 records from Museu Paraense Emilio Goeldi - ichthyology Collection. 2 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 1 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 20 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 12870 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 23637 records from SA Fauna (BDBSA). 1610 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" (1989-1996). 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 3 records from Specimens from India at the University Museum at the University of Bergen. 355 records from Ichthyologie ZMK. 57 records from MVZ Hildebrand Collection (Arctos). 4933 records from Lund Museum of Zoology (MZLU). 164 records from Données ONF Faune-Flore-Fonge. 1 records from Vermes ZMK. 5 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 1 records from CAS Invertebrate Zoology (IZ). 4410 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 3561 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 19 records from The first case of aggressive mimicry among lamprologines in a new species of Lepidiolamprologus (Perciformes: Cichlidae) from Lake Tanganyika.. 10 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 200 records from Zoological collection of the National Museum. 398 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 1277 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 2786 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 9 records from Corumbataia britskii (Siluriformes: Loricariidae: Hypoptopomatinae) a new species from the upper Rio Parana basin, Mato Grosso do Sul, Central Brazil.. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 9574 records from Norwegian Biodiversity Information Centre - Other datasets. 19700 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 23 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 7 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 1 records from Naturalis Biodiversity Center (NL) - Mammalia. 326657 records from Museum of Comparative Zoology, Harvard University. 1 records from Naturalis Biodiversity Center (NL) - Cnidaria. 60 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 16 records from Moenkhausia pankilopteryx, new species from rio Tocantins drainage, Brazil (Ostariophysi: Characiformes, Characidae).. 5393 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 194048 records from Ichthyology Collection - Royal Ontario Museum. 115467 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 595 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 3299 records from Tasmanian Museum and Art Gallery provider for OZCAM. 3014 records from Monitoring data from the federal state Hesse (Germany). 2984 records from Colección de Peces Universidad Católica de Oriente. 19269 records from iNaturalist research-grade observations. 8424 records from National Taiwan University. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 45 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 635 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 209 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 1070 records from BioGIS - Fish - HUJ collections. 23 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 2 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 5 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 45410 records from observe_tuna_bycatch_ecoscope. 11 records from A new rainbowfish (Teleostei: Melanotaenioidei: Bedotiidae) from the southeastern highlands of Madagascar, with comments on the biogeography of Bedotia.. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 164 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 7 records from Invertebrates Collection of the Swedish Museum of Natural History. 10091 records from KUBI Ichthyology Tissue Collection. 13 records from Alien Species in Poland - Animals. 107 records from Estonian Museum of Natural History. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 999 records from National Museum Of Marine Science & Technology. 2957 records from Bolivian Amazon lowland fish metacommunity data. 8492 records from University of California Museum of Paleontology. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 7 records from Kryptolebias sepia n. sp. (Actinopterygii: Cyprinodontiformes: Rivulidae), a new killifish from the Tapanahony River drainage in southeast Surinam.. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 4703 records from KUBI Vertebrate Paleontology Collection. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 34006 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1295 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 556 records from Countryside Council for Wales - Shad Monitoring data. 16553 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 198608 records from CAS Ichthyology (ICH). 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 9 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 18 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 401094 records from NMNH occurrence DwC-A. 5963 records from Census of the animals of Benin. 1980 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 14096 records from NCSM Vertebrate Paleontology Collection. 202 records from infish. 17446 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 24 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 6615 records from Monitoring data from the federal state Saxony (Germany). 57159 records from TNHC Ichthyology Collection. 634 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 5 records from Siegen/ Gymnasium Am Löhrtor. 2 records from Spechtwald. 1 records from Kremmer Luch. 1 records from Fledermaus. 3 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 1 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 1 records from Roter Berg Werdau (Leubnitz). 8 records from Föhrenried (Fronreute und Baindt). 1 records from Artenvielfalt Kreis Gießen. 5 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 2 records from Regenrückhaltebecken (Zeulenroda). 1 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 3 records from Zielbach (Töll). 1 records from Zitadelle Berlin-Spandau (7b). 1 records from Kabelskebach (Kabelsketal, Saalkreis). 1 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 18 records from Triebesbach (Zeulenroda-Triebes). 2 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 3 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 4 records from Umgebung der Grundschule Oderberg. 1 records from Die Wuhle. 6 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1 records from Alter Kreidebruch Saßnitz/Rügen. 17 records from Schussenaue bei Berg. 1 records from Rund um das LUGY. 1 records from Wassermann. 1 records from Varnhalt. 1 records from Rund ums Ökohaus (Würzburg). 1 records from Artenvielfalt im Beckerbruch (Dessau). 2 records from Wasserwerkspark (Chemnitz). 3 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 1 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 1 records from Selztal bei Friesenheim. 1 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 2 records from Uferzone Wipper (Biesenrode). 1 records from Gieselbachtal Fulda-Harmerz. 1 records from Isartal Dingolfing. 2 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 1 records from Naturerlebnisraum Koppelsberg (Plön). 4 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 1 records from Gelände des Schulzentrums am Himmelsbarg. 1 records from Biosphäre Bliesgau. 1 records from NABUGEO1. 6 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 1 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 3 records from Zoo Frankfurt. 3 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 1 records from Kinderbauernhof Pinke-Panke. 2 records from Stausee Weiditz. 1 records from LSG "Großes Bruch". 1 records from Römertal (Steinpleis). 1 records from Riedkanal Bötzingen. 9 records from Stadtpark Schmölln. 47 records from Revised diagnosis of the genus Bangana Hamilton, 1822 (Pisces: Cyprinidae), with taxonomic and nomenclatural notes on the Chinese species.. 1 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 2 records from Tauchen und Meer 02. 5 records from Draubiotop Lavamünd. 5 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 4 records from Issumer Fleuth. 5 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 14 records from Sudeniederung (Amt Neuhaus). 1 records from AKG-Gelände in Bensheim. 2 records from Brenz (Heidenheim). 14 records from Three new species of the seasonal killifish genus Simpsonichthys, subgenus Hypsolebias (Teleostei: Cyprinodontiformes: Rivulidae) from the rio Paracatu drainage, rio São Francisco basin, Brazil.. 2 records from Olympiapark (München). 2 records from Lerchenauer Baggersee (München). 1 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 1 records from Mikroorganismen. 6 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 2 records from Kinderwald Hannover. 1 records from Im und um das Schulhaus. 1 records from Wattenmeer-Safari (Wurster Watt). 1 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 14 records from Tauchen und Meer. 15898 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 1 records from Tag der Artenvielfalt am Bruckenwasen. 4 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 1 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 2 records from Kaniswall/ Gosener Wiesen an der Spree. 1 records from Expedition "Schulgelände". 5 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 2 records from LK 11 im Mönchspark. 1 records from Tag der Artenvielfalt in Heidelberg. 1 records from Tongrube bei Hettstedt. 2 records from FFH-Gebiet Klosterwasser/Burkau. 1 records from Gronau - auf der Suche nach dem Neunauge. 1 records from Tornoer Teich. 2 records from Liether Kalkgrube. 10 records from Rund um den Hainbergsee. 1 records from "Ahrschleife bei Altenahr". 1 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 1 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 4 records from BUND Naturschutzzentrum St. Julian. 3 records from Art´n Vielfalt im Kinderwald. 2 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 21 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 11 records from Balantiocheilos ambusticauda, a new and possibly extinct species of cyprinid fish from Indochina (Cypriniformes: Cyprinidae).. 6 records from Status of the genus Macroramphosus (Syngnathiformes: Centriscidae) in the eastern Mediterranean Sea.. 2040 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 50 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 17 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 235 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 17 records from Biodiversity records from Ireland - general. 95 records from Marine Biological Association - DASSH Data Archive Centre expert sighting records. 18527 records from Diveboard - Scuba diving citizen science observations. 39194 records from Continuous Plankton Recorder Dataset (SAHFOS). 1171 records from Glasaalmigratie - Glass eel migration in the river Yser. 52021 records from Freshwater fishes of Italy. 107 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 22 records from Ireland's BioBlitz 2012. 269 records from The species of the Hypostomus cochliodon group (Siluriformes: Loricariidae).. 2 records from Typhlichthys eigenmanni Charlton, 1933, an available name for a blind cavefish (Teleostei: Amblyopsidae), differentiated on the basis of characters of the central nervous system.. 44483 records from Atlas of Danish Fishes. 65 records from Naturalis Biodiversity Center (NL) - Diptera. 2109 records from Colección Ictiológica del CENPAT-CONICET. 2 records from SMNS Palaeontological collection - Invertebrates (Jurassic and Cretaceous). 3744 records from naturgucker. 2005 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 7 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 5 records from A new species of Nanochromis (Teleostei: Cichlidae) from Lake Mai Ndombe, central Congo Basin, Democratic Republic of Congo.. 268833 records from Biological Records Centre - Database for the Atlas of Freshwater Fishes. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 573 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 234 records from Clyde River Foundation - Allis Shad (Alosa alosa) distribution for Scotland, historical to present. 24 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 16 records from National Trust - Hatfield Forest species data held by The National Trust.. 11 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 1 records from Dorset Environmental Records Centre - Ross Coral Mapping Project - NBN South West Pilot Project Case Studies. 6 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from the Andean Cordillera of Perú with comments on relationships within the genus.. 165 records from Natural England - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by English Nature. 1 records from Meiobenthos investigations in the Black Sea during Poseidon cruise PO317/3. 312 records from Benthos counted on dredged samples during Valdivia cruise VA44. 706 records from Benthos counted on dredged samples during Valdivia cruise VA53. 107 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 4 records from Herpetology Collection. 4 records from Biosphärenpark Wienerwald - Pfaffstätten. 2 records from GEO-Hauptveranstaltung in "Wildtierland". 2 records from Die Bachspezies 2008/2009. 1 records from Ökosysteme rund um Wedel. 11 records from Mangfalltal. 1 records from GEO-Tag am Hohlen Stein. 1 records from Grünanlagen Stadt Brandenburg an der Havel. 1 records from Zwischen Enz und Schule. 1 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 3 records from Artenvielfalt im Rhein-Neckar-Raum. 6 records from Schanzenanlage Bergham. 1 records from Von Elf bis Elf" Der Botanische Garten Wuppertal. 1 records from Dornwanger Moos. 1829 records from UMZC Zoological Specimens. 1 records from Wälder bei Nordkirchen. 1 records from Schloss Fasanerie Eichenzell. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 1 records from Naturpark Kottenforst-Ville 17.6.09. 1 records from Raus in die Natur. 1 records from Rund ums Schulgelände. 1 records from NABU-Fläche am Bösselhausener Weg. 1 records from Leben in den Elbwiesen. 27 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 2639 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 1711 records from Fish specimens of Natural History Museum, Kishiwada City. 2867 records from Mammal and Fish speciemens of Kumamoto City Museum. 55761 records from Fish Specimens. 3 records from Tissues Specimens. 1 records from MfN - Fossil invertebrates Ia. 216 records from MfN - Fossil vertebrates III. 2114 records from BioMar - LIFE project. 2 records from MfN - Fossil invertebrates III. 10 records from MfN - Fossil vertebrates IV. 1 records from MfN - Fossil plants (Cenophytic). 2 records from MfN - Fossil plants (Mesophytic). 32 records from Museu Paraense Emilio Goeldi - Ornithology Collection. 456 records from Øvre Heimdalsvatn, Radiocaesium (Cs-137) monitored annually in brown trout (Salmo trutta). 1621 records from SBMNH Vertebrate Zoology. 9 records from A new species of the loricariid catfish genus Hemipsilichthys from southern Rio de Janeiro coastal rivers, southeastern Brazil (Teleostei: Siluriformes).. 74 records from Description of a new Batrochoglanis species (Siluriformes, Pseudopimelodidae) from the rio Paraguai basin, State of Mato Grosso, Brazil.. 13201 records from Colección Ictiológica del Instituto Alexander von Humboldt. 24 records from Taxonomy and phylogenetic relationships among species of the seasonal, internally inseminating, South American killifish genus Campellolebias (Teleostei: Cyprinodontiformes: Rivulidae), with the description of a new species.. 3 records from Merseyside BioBank - Merseyside BioBank NBN Frequently Updated Taxa. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 3 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 2 records from Rådgivende Biologer. 1 records from BioBlitz Barcelona 2010-14. 964 records from Environment Agency - Environment Agency Non-native Species records v1. 39280 records from Northern Territory Museum and Art Gallery provider for OZCAM. 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 2 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 2 records from AlgaTerra. 163771 records from LACM Vertebrate Collection. 739 records from Natural History Museum Rotterdam (NL) - Chordata collection. 6252 records from Colección Ictiológica del Río Bravo en México (UANL). 302 records from Insecta ZMK. 1 records from Bayerische Donau - Riedlingen. 1 records from Bayerische Donau - Tapfheim. 1 records from Fluss - Vielfalt. 1 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 1 records from Grünes Germersheim. 1 records from Tauchaktion. 1 records from Wuhle - Brücke / B1. 1 records from Wuhle - Brücke/ Mosbacher Straße. 95343 records from Image Database of Fishes in the Kanagawa Prefectural Museum of Natural History. 100 records from Fish (MNHM-PI). 1614 records from Fish (ASJK-PI). 99 records from Fossil (WSHN-FO). 7486 records from Fish (KIWE-PI). 912 records from Fish (JNHM-PI). 106078 records from Fish (NSMK-PI). 2524 records from Fish (NHMK-PI). 328 records from Weddell Sea macrozoobenthos EASIZ I. 57 records from Icota - Pelagant. 162 records from Antarctic fish Gobionotothen gibberifrons. 174 records from South American Antarctic Marine Biodiversity Literature. 70 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 2 records from RMT Trawl catch from the 1983/84 V5 ADBEX II voyage. 184 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 48 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 34 records from Two new species of Pseudecheneis, rheophilic catfishes (Teleostei: Sisoridae) from Nepal.. 1 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE262. 3 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE241. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE218. 12 records from (Table 1.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Polarstern cruise ANT-XXIII/7. 22 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 51319 records from Western Australian Museum provider for OZCAM. 436 records from Larval fish at Helgoland Roads in 2005. 38 records from EDIT - ATBI in Spreewald (Germany). 22 records from Geophagus abalios, G. dicrozoster and G. winemilleri (Perciformes: Cichlidae), three new species from Venezuela.. 2377 records from SysTax - Zoological Collections. 4 records from Neolamprologus devosi sp. n., a new riverine lamprologine cichlid (Teleostei, Cichlidae) from the lower Malagarasi River, Tanzania.. 429 records from Larval fish at Helgoland Roads in 2004. 176 records from Larval fish at Helgoland Roads in 2003. 137955 records from Natural History Museum (London) Collection Specimens. 1 records from SMNS Palaeontological collection - Invertebrates (Cenozoic). 1 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 1 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 1 records from Clitellata - SMF. 111 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 2 records from Natural History Museum, Vienna - Herbarium W. 378 records from Occurrences des observations de la campagne Suivi Aérien de la Mégafaune Marine en France métropolitaine (SAMM1 - Hiver 2011/2012). 246 records from Repatriación del material ictiológico de 12 estados de la República Mexicana, depositado en la colección ictiológica de la Universidad de Tulane, E.U.. 2398 records from Macaulay Library Audio and Video Collection. 3478 records from Especies de peces introducidas en aguas continentales de México. Catálogo y manuscrito. 1000 records from Colección de los peces nativos de Sonora. 999 records from Biodiversidad y dinámica espacio-temporal del ictioplancton de dos sistemas lagunares de la Reserva de la Biósfera de Sian Ka'an. 766 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Peces. 3312 records from Base de datos sobre ictioplancton para la Bahía de Campeche, México. 2427 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. Larvas de Peces. 751 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 678 records from Ictiofauna de los ríos Papagayo, Atoyac y Coyuca. 57379 records from NatureServe Network Species Occurrence Data. 91 records from Genética y taxonomía de los robalos (Centropomus spp) del golfo de California, México. 1444 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 1134 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 236 records from Los peces del área oaxaqueña de la Reserva de la Biosfera Tehuacán-Cuicatlán. 431 records from Ictiofauna del sistema lagunar costero Chacahua-La Pastoría, Oaxaca. 816 records from Peces de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 307 records from Diversidad y distribución de las comunidades de peces de ríos y lagunas del volcán San Martín de la reserva de la biósfera Los Tuxtlas. 327 records from Elaboración de las fichas técnicas para la evaluación del riesgo de extinción de 18 especies de peces dulceacuícolas mexicanos. 953 records from Ictiofauna insular del medio y bajo Golfo de California. 310 records from Ictiofauna en cenotes del ejido maya "Xhazil Sur y Anexos" y de la reserva de Sian Ka'an, Q. Roo, México. 1358 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 2205 records from Evaluación de la ictiofauna en las áreas focales del corredor biológico costero-Yucatán. 164 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Peces. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 2122 records from Diversidad de peces de las lagunas costeras de Pueblo Viejo y el Mango, Veracruz. 190 records from Ireland's BioBlitz. 3559 records from Actualización de bases de datos de peces. 5608 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 2 records from Diversidad bentónica de la laguna Celestún, Yucatán. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 731 records from Análisis del ictioplancton de la reserva faunística de Ría Lagartos, Yucatán. 72 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 1081 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 610 records from Ictiofauna de la Bahía de Banderas Nayarit, Jalisco y zonas adyacentes, México. 160 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 91 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1168 records from Registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 2192 records from Diversidad dinámica y patrones reproductivos en la comunidad de peces demersales del Golfo de Tehuantepec. 817 records from Inventario de la biota marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 43768 records from Ichthyology, Kagoshima University Museum. 459 records from Akita Prefectural Museum＋Actinopterygius Specimens of Akita Prefectural Museum. 5 records from Harold W. Manter Laboratory of Parasitology Collection. 1417 records from Ibaraki Nature Museum, Fish collection. 26656 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 646 records from IG TUT paleontology. 9 records from Tartu University, palaeontology collections. 1179 records from RBINS collections. 99032 records from Ohio State University Fish Division (OSUM). 1626 records from Ichthyology Collection - CONICET- Argentina. 513 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 525 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 208 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 624 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Tridens00/5. 198 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 1 records from Herpetology Collection - Instituto Nacional de Pesquisas da Amazônia. 7322 records from Distribution of 15 major fish species in the North Sea between 1959 and 1979. 363912 records from VIS - Fishes in inland waters in Flanders, Belgium. 27270 records from Collection Ichthyologie - SNSD. 73 records from Röntgenarchiv Wilhelm Stürmer - SMF. 1 records from Collection Crustacea - SNSD. 182 records from Collection Anatomie Histologie - SMF. 2 records from MfN - Heteroptera Collection. 18 records from SOMBASE. 15 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 202 records from The Korean Freshwater Fishes. 41875 records from Canadian Museum of Nature Fish Collection. 140660 records from UWFC Ichthyology Collection. 1 records from Colección Paleontológica Invertebrados e Icnologia - CONICET- Argentina. 1 records from PIROP (Shipboard Surveys). 25933 records from Freshwater fish collection. 6234 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 196291 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 81 records from EPA'S EMAP Database. 154240 records from HMAP-History pf Marine Animal Populations (CoML). 34293 records from NODC WOD01 Plankton Database. 4786 records from SeamountsOnline (seamount biota) (CoML). 15882 records from Southampton Oceanography Center Discovery Collections Midwater Database. 36 records from Natural Geography In Shore Areas (NaGISA) Dataset. 1 records from NBI. 244377 records from North Pacific Groundfish Observer (North Pacific Research Board). 3027 records from Gulf of Maine Bottom Trawl Survey Data (NEFSC,NMFS,NOAA)(USOBIS). 5438 records from Bishop Museum Data (OBIS distribution) (USOBIS). 9387 records from SEAMAP - marine mammals, birds and turtles. 94027 records from Atlantic Reference Centre (OBIS Canada). 2928 records from Electronic Atlas of Ichthyoplankton on the Scotian Shelf of North America (OBIS Canada). 28909 records from Canadian Museum of Nature - Fish Collection (OBIS Canada). 65 records from Atlantic Canada Conservation Data Centre (OBIS Canada). 2 records from Luzonichthys seaver, a new species of Anthiinae (Perciformes, Serranidae) from Pohnpei, Micronesia. 498 records from Nova Scotia Museum of Natural History - Marine Birds, Mammals, and Fishes (OBIS Canada). 101 records from Bay of Fundy Species List (OBIS Canada). 383978 records from ECNASAP - East Coast North America Strategic Assessment (OBIS Canada). 172 records from Davis Strait and Baffin Bay Zooplankton (OBIS Canada). 59 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 113100 records from Pacific Ocean Shelf Tracking (OBIS Canada). 282088 records from ``South Western Pacific Regional OBIS Data provider for the NIWA Marine Biodata Information System``. 289 records from ChEssBase (CoML). 93406 records from CSIRO Marine Data Warehouse (OBIS Australia). 1131 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 561 records from MedOBIS (EurOBIS). 49 records from BioMar (EurOBIS). 4 records from Macrobel: Long term trends in the macrobenthos of the Belgian Continental Shelf (EurOBIS). 303 records from A comparison of benthic biodiversity in the North Sea, English Channel and Celtic Seas (EurOBIS). 1226 records from Demersal and pelagic species from the Patagonian shelf (OBIS South America, SOUTHERN OCEAN SUB-NODE). 1574 records from REVIZEE South Score / Pelagic and Demersal Fish Database (OBIS South America, BRAZIL). 19 records from MarBEF Publication Series data (EurOBIS). 318 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fish. 3882 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 4097 records from REVIZEE South Score / Pelagic and Demersal Fish Database II (OBIS South America, BRAZIL). 1391 records from Centro Nacional Patagonico Ichthyological Collection (OBIS South America, SOUTHERN OCEAN SUB-NODE). 3311 records from Fishes in the Argentine Sea from 1967 to the present time (OBIS South America, SOUTHERN OCEAN SUB-NODE). 118 records from AIMS - Bioresources Library (OBIS Australia). 2589 records from MAR-ECO (EurOBIS). 43817 records from Bureau of Rural Sciences National commercial fisheries half-degree data set 2000-2002 (OBIS Australia). 98067 records from South African Institute for Aquatic Biodiversity - Fish Collection (AfrOBIS). 13250 records from iziko South African Museum - Fish Collection (AfrOBIS). 155 records from Posidonia Oceanica Survey 2005 (EurOBIS). 32126 records from AIMS - Baited Remote Underwater Video Station (OBIS Australia). 5313 records from National Institute of Marine Sciences and Technologies - Trawl Surveys (AfrOBIS). 5085 records from Marine and Coastal Management - Demersal Surveys (years 1983-1985) (AfrOBIS). 32975 records from Marine and Coastal Management - Demersal Surveys (years 1986-1990) (AfrOBIS). 41186 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 10797 records from Marine and Coastal Management - Demersal Surveys (years 1996-2000) (AfrOBIS). 21265 records from Marine and Coastal Management - Demersal Surveys (years 2001-2005) (AfrOBIS). 5535 records from Marine and Coastal Management - Demersal Surveys (years 2006-) (AfrOBIS). 38237 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 41766 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1985) (AfrOBIS). 66380 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1986) (AfrOBIS). 53975 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1986) (AfrOBIS). 78567 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 59999 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1987) (AfrOBIS). 77228 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1988) (AfrOBIS). 54195 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 77761 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1989) (AfrOBIS). 55703 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1989) (AfrOBIS). 59596 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2000) (AfrOBIS). 41858 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2000) (AfrOBIS). 53015 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2001) (AfrOBIS). 29424 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2001) (AfrOBIS). 28071 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 22969 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2002) (AfrOBIS). 22728 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2003) (AfrOBIS). 20206 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2003) (AfrOBIS). 32502 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2004) (AfrOBIS). 25183 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2004) (AfrOBIS). 27726 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2005) (AfrOBIS). 21337 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2005) (AfrOBIS). 60684 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1999) (AfrOBIS). 47402 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 65117 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1998) (AfrOBIS). 54584 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1998) (AfrOBIS). 68854 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1995) (AfrOBIS). 53936 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 65719 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1996) (AfrOBIS). 47869 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1996) (AfrOBIS). 60552 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1997) (AfrOBIS). 47539 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1997) (AfrOBIS). 1 records from Naturalis Biodiversity Center (NL) - Coleoptera. 62 records from Mammalia - Baekdu Mountain Animal (KIDR-MM). 8045 records from MSUM Ichthyology and Herpetology Collections. 4795 records from Paleobiology Database. 35934 records from Fish Collection of Yokosuka City Museum. 57576 records from Fish Collection of Hokkaido University. 16501 records from Fish Specimens of Museum of Tokushima Prefectural Museum, Japan. 42078 records from Fish specimens of Fisheries Research Laboratory Mie University. 46849 records from Fish specimen database of Osaka Museum of Natural History. 35460 records from Fish collection of National Museum of Nature and Science. 29859 records from Freshwater Fish Specimens of Lake Biwa Museum. 101 records from Individual Sightings. 37986 records from rmca-albertine-rift-cichlids. 5980 records from Arctic Ocean Diversity. 967 records from IIAPPoa. 32750 records from Fish tag database. 125657 records from Fish specimens. 6 records from Relationships of the New World cichlid genus Hypsophrys Agassiz 1859 (Teleostei: Cichlidae), with diagnoses for the genus and its species.. 75 records from Galathea II, Danish Deep Sea Expedition 1950-52. 9 records from Nivå Bay species list, Zealand, Denmark. 14 records from Priest Pot species list, Cumbria, Britain. 68221 records from The Fish Collection. 2555 records from Database Schema for UC Davis Wildlife museum. 25518 records from FHSM Fish Collection. 10357 records from University of Alberta Ichthyology Collection (UAMZ). 13068 records from CNPE/Coleccion Nacional de Peces. 14363 records from UNSM Vertebrate Specimens. 1 records from Mammal tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 1953 records from Fish tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 13 records from Invertebrate Paleontology Division, Yale Peabody Museum. 3 records from Invertebrate Zoology Division, Yale Peabody Museum. 1 records from Algaterra Types. 14 records from GEO Biodiversity Day. 10253 records from Biologiezentrum Linz. 980 records from Israel Nature and Parks Authority. 2840 records from Banc de dades de biodiversitat de Catalunya-VerteCat. 4085 records from IndOBIS, Indian Ocean Node of OBIS. 53646 records from Pelagic Fish Observations 1968-1999. 1 records from invertebratezoology. 12876 records from Fish Collection of Natural History Museum and Institute, Chiba. 495 records from Life Science National Tsing Hua University. 2 records from Museu Paraense Emilio Goeldi - Ophidia Collection. 189 records from Fish larvae biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 340 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 348 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 849 records from NOAA HML Tidal Creek Database. 84207 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1990) (AfrOBIS). 58311 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1990) (AfrOBIS). 76100 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1991) (AfrOBIS). 57498 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1991) (AfrOBIS). 74391 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 67189 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1992) (AfrOBIS). 81163 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1993) (AfrOBIS). 56593 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1993) (AfrOBIS). 58126 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1994) (AfrOBIS). 54545 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1994) (AfrOBIS). 28713 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 1372 records from MfN Fish Collection, Zoology. 113 records from inatura - Erlebnis Naturschau Dornbirn. 145 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage. 50 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage. 163 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 20 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 25529 records from Pelagic Fish Observations 1968-1999 (Australian Antarctic Data Centre). 1460 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 1 records from Atlantic and Gulf Rapid Reef Assessment - Fish (OBIS Australia). 41695 records from AIMS LTM Fish (OBIS Australia). 906 records from Northern Barrier Marine Life (OBIS Australia). 118140 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations (OBIS Canada). 4 records from NCOS1959_Crustacea (OBIS China). 2 records from NCOS1959_Mollusca (OBIS China). 19 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82 (Australian Antarctic Data Centre). 85 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage (Australian Antarctic Data Centre). 248 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage (Australian Antarctic Data Centre). 283 records from Freshwater fish Specimens of Taga Town Museum, Shiga Pref., Japan. 67 records from Characidium longum (Characiformes: Crenuchidae), a new fish from Venezuela.. 2 records from Herp Collection. 908 records from Rare marine fishes taken in Irish waters from 1786 to 2008. 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 2 records from Schistura papulifera, a new species of cave loach from Meghalaya, India (Teleostei: Balitoridae).. 3 records from Petroscirtes pylei, a new saber-toothed blenny from the Fiji Islands (Teleostei: Blenniidae).. 777 records from RAVON (NL) - Fish observations extracted from Hoek (1890) and Redeke (1921). 70 records from Staffordshire Ecological Record - SER Site-based Surveys. 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 6 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Fish. 23763 records from Colección Nacional de Peces del IBUNAM. 3408 records from UCM Fish Collection (Arctos). 20 records from UCM Amphibian and Reptile Collection (Arctos). 150 records from UC Davis Department of Anthropology Museum. 19 records from BÜG. 1 records from Am Moosangerweg. 2 records from AKG-Gelände (Bensheim). 2 records from FFH-Gebiet Ahrbachtal. 1 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 17 records from Hamberger Brücke / Würmtal (Pforzheim). 5 records from Mooswald (Freiburg). 12 records from Gemeinde Sursee. 3 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 5 records from Schlern - (Bozen). 2 records from GEO Hauptveranstaltung Tirol (Innsbruck). 2 records from Zukünftiges NSG Höftland/Bockholmwik. 2 records from Freiburger Tag der Artenvielfalt. 1 records from Langes Tannen (Uetersen). 11 records from Stausee (Oberdigisheim/Meßstetten). 2 records from Erlengraben/Lipp-Tal (Östringen). 4 records from NSG Karwendel. 10 records from Neckartalsüdhang (Horb). 2 records from Umgebung der Gesamtschule Hamburg-Winterhude. 37 records from Artenvielfalt der Nordsee - Helgoland. 42 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 3 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from katzenbuckel. 1 records from Promberg1. 12 records from GEO-Hauptveranstaltung (Duisburg). 13 records from Wanderweg am Windebyer Noor (bei Eckernförde). 14 records from BUND - Dassower See (Lübeck/Dassow). 12 records from Wildes Bremer Leben im Park. 2 records from Entdeckertour am Muldestausee. 9 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 9 records from Leegmoor (Moormerland/Leer). 2 records from Unser Schulgelände. 22 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 31 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 11 records from Tag der Artenvielfalt in der Stadt Luzern. 21 records from Nottekanal, Klasse 7 - 10. 5 records from Luch Niederlehme, Schüler der Klasse 7. 5 records from Stadtbiotop Ulrichteich. 12 records from Pilstingermoos. 5 records from Artenfülle um das Schalkenmehrener Maar. 13 records from Riedensee. 1 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 1 records from Hüttenseepark (Meißendorf). 1 records from Schaalbach. 19 records from GEO-Hauptveranstaltung Bodden (Vilm). 17132 records from LSUMZ (LSU MNS) Fishes Collection. 1 records from Pottundkopp. 4 records from Knechtweide (Kohlfurth). 2 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 11 records from Kiesbagger (Mittelhausen). 1 records from Schloß Türnich (Kerpen). 1 records from Quarrendorfer Landschaftsschutzgebiet. 1 records from Schulprojekt (Bremen). 1 records from Fuldaaue (Stadtgebiet Fulda). 1 records from Muehlenbach bei Friesheim. 1 records from Renaturierung Werse (Innenbereich Beckum). 2 records from Bergkamen- Bergehalde Großes Holz. 1 records from Stadt Königs Wusterhausen. 2 records from Stadtpark Sulzbach-Rosenberg. 1 records from Lindau im Bodensee. 1 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 1 records from Schulhof und Anlagensee in Nellingen. 3 records from Tiergarten Straubing. 1 records from Vorderer Tiergarten (Dessau). 3 records from Werremündung im Schwarzatal. 8 records from Eppingen und Umgebung. 3 records from Weidenhüttendorf an der Würm (München). 4 records from Prophetensee Quickborn. 2 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 10 records from Schussenaue (Weingarten). 11 records from Wupperaue bei Kemna (Wuppertal). 2 records from An der Ohm, (Wettsaasen). 10 records from Artenvielfalt der Nordsee - Sylt. 2 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 1 records from Walldorf-Wiesloch: "Natur über den Gleisen". 1 records from Innenstadt Göttingen - Natur Zuhause. 3 records from Mißmahlsche Anlage. 1 records from Teich Berlin Wuhlheide. 1 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 1 records from Unna-Mühlhausen, Wiesen. 119 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 30 records from A new species of Farlowella Eigenmann and Eigenmann (Siluriformes: Loricariidae), a stickcatfish from Bolivia.. 6 records from Moema apurinan sp. n. and Aphyolebias boticarioi sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new annual killifishes from the Rio Purus basin, Brazilian Amazon.. 519 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 3496 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 1 records from UTA Herpetology. 4 records from Description of a new species of Labeo (Teleostei: Cyprinidae) from the lower Congo River.. 959 records from SMNS Palaeontological collection - Fossil aquatic vertebrates. 2 records from Nematode abundance in cold seep sediments of the Darwin mud volcano. 12 records from Caracterización de la Íctiofauna presente en la laguna Concepción, Bocana del río Saija (Cauca), sitio sagrado de las comunidades Indígenas de OZBESCAC. 41056 records from KUBI Ichthyology Collection. 127 records from Natural History Museum, University of Tartu. 23 records from Oligosarcus perdido (Characiformes, Characidae), a new species of freshwater fish from Serra da Bodoquena, upper Rio Paraguai basin, Brazil.. 28 records from Hypostomus macushi, a new species of the Hypostomus cochliodon group (Siluriformes: Loricariidae) from Guyana.. 22 records from Akrokolioplax, a new genus of Southeast Asian labeonine fishes (Teleostei: Cyprinidae).. 1831 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 1614 records from Fish (ASJK-PI). 6 records from Natural England - Invertebrate Site Register - England.. 21 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 6 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 765 records from Global subterranean fishes. 16 records from SuLaMa blind cave fish occurence data. 5 records from Xanthichthys greenei , a new species of triggerfish ( Balistidae ) from the Line Islands. 186 records from University Marine Biological Station Millport - 1999-2009 UMBSM Clyde Sea Fairlie Channel Beam Trawl Survey. 1 records from Greater Manchester Ecology Unit - Distribution of Species of Conservation Interest in Greater Manchester. 2304 records from Fundación Miguel Lillo - Colección Ictiológica. 11611 records from New Mexico Biodiversity Collections Consortium database. 1 records from Perchtoldsdorfer Heide. 6 records from Naturpark Drömling. 7 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 8 records from Berkel. 463 records from Sponges of Rathlin Island. 7 records from Lustadter Wald .. 10 records from Kohlstattbrunnental. 40046 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 300 records from Gunma Museum of Natural History, Fish Specimen. 5 records from Artenvielfalt am Schlern. 201124 records from Tulane University Museum of Natural History. 71908 records from North Carolina State Museum of Natural Sciences Fishes Collection. 3423 records from Biological and palaeontological collection and observation data MNHNL. 973 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 9 records from COMARGIS: Information System on Continental Margin Ecosystems. 1 records from Botany Division, Yale Peabody Museum. 27399 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 2 records from Paleobotany Division, Yale Peabody Museum. 3157 records from Vertebrate Paleontology Division, Yale Peabody Museum. 301 records from BIOLOGICAL SCIENCES DATA. 32370 records from Collection Pisces SMF. 1 records from Collection Porifera SMF. 525 records from Collection Agnatha fossil SMF. 47 records from A preliminary inventory of the catfishes of the lower Rio Nhamundá, Brazil (Ostariophysi, Siluriformes). 174 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 4 records from Type Localities for organisms and fossils first described from Antarctica. 378 records from Fish catch from 1996/97 Voyage 2 WASTE (WOCE Antarctic Southern Transect Expedition). 17 records from AMNH Bird Collection. 17 records from A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China.. 40 records from Two new cichild species Neolamprologus (Teleostei: Cichlidae) from Lake Tanganyika, East Africa.. 1 records from Scottish Environment Protection Agency - River macroinvertebrate data for 2005 and 2006. 66 records from UAM Earth Sciences Collection (Arctos). 24 records from A new genus and two new species of congrid eels (Teleostei: Anguilliformes: Congridae) from the Indo-West Pacific, with a redescription and osteology of Chiloconger dentatus.. 404 records from Fish Living in Freshwater (KIDR-PI). 2524 records from Fish (NHMK-PI). 25 records from Hemiodus jatuarana, a new species of Hemiodontidae from the rio Trombetas, Amazon Basin, Brazil (Teleostei, Characiformes).. 3 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 451 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 81 records from Revision of the snailfish genus Allocareproctus Pitruk & Fedorov (Teleostei: Liparidae), with descriptions of four new species from the Aleutian Islands.. 7 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 4 records from A new and presumably extinct species of Ptychochromoides (Teleostei: Perciformes: Cichlidae) from central Madagascar.. 22 records from A new species of snapper (Perciformes: Lutjanidae) from Brazil, with comments on the distribution of Lutjanus griseus and L. apodus.. 1 records from SMNS Palaeontological collection - Palaeozoic and triasic invertebrates. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 65531 records from SLU Aqua Institute of Freshwater Research Swedish Electrofishing Registry - SERS. 278 records from A review of the species in the Apogon fasciatus group with a description of a new species of cardinalfish from the Indo-West Pacific (Perciformes: Apogonidae).. 99 records from Fossil (WSHN-FO). 1 records from Bird Specimens. 196 records from Reptiles, Amphibians and Fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 8 records from A new glanapterygine catfish of the genus Listrura (Siluriformes: Trichomycteridae) from the southeastern Brazilian coastal plains.. 9 records from Austrolebias univentripinnis sp. nov. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the Mirim Lagoon basin, southern Brazil.. 7 records from Vascular Herbarium, NMBU. 312 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 7 records from Wetland Inventory (NV). 2 records from Herps Specimens. 29 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 33 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from the Temburong River basin, Brunei Darussalam, Borneo.. 29 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 43 records from Bryconops magoi and Bryconops collettei (Characiformes: Characidae), two new freshwater fish species from Venezuela, with comments on B. caudomaculatus (Gunther).. 1155 records from Limnodata. 39 records from Naturalis Biodiversity Center (NL) - Porifera. 5 records from National Trust - Sutton Hoo species data held by The National Trust.. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 3 records from Rivulus mahdiaensis, a new killifish from central Guyana (Cyprinodontiformes: Rivulidae).. 144 records from Taxonomy of the South American genus Pachypops Gill 1861 (Teleostei: Perciformes: Sciaenidae), with the description of a new species.. 38 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 4 records from Faun. 84903 records from NINA Vanndata fisk. 76 records from Fish (MNHM-PI). 397 records from condoncollection. 14 records from Two new glyptosternine catfishes (Teleostei: Sisoridae) from Vietnam and China.. 2012 records from Caracterización morfométrica del bagre rayado para la cuenca del Magdalena. 8 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 35898 records from Queensland Museum provider for OZCAM. 31 records from Description of a new species of the fish genus Acanthoplesiops Regan (Teleostei: Plesiopidae: Acanthoclininae) from Tonga.. 1 records from CUMV Amphibian Collection (Arctos). 269 records from ArtenFinder. 5630 records from Inland Fisheries Ireland data on freshwater fish in Irish lakes. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 335 records from Revision of the South American freshwater genus Plagioscion (Teleostei, Perciformes, Sciaenidae).. 25 records from A new Gymnotus (Teleostei: Gymnotiformes: Gymnotidae) from the Pantanal Matogrossense of Brazil and adjacent drainages: continued documentation of a cryptic fauna.. 24 records from National Trust - Ickworth species data held by The National Trust.. 220033 records from Geographically tagged INSDC sequences. 10 records from Description of the larval stages of the Shield Darter, Percina peltata (Pisces: Percidae), in New York.. 1690 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 37812 records from Royal Museum of Central Africa - Albertian Rift Cichlids (ENBI wp13). 66 records from Fieldjournal.org observation database. 1 records from SMNS Palaeontological collection - Amphibians, reptiles (Palaeozoic, Mesozoic). 40 records from The identity of Pseudecheneis sulcata (M'Clelland, 1842), with descriptions of two new species of rheophilic catfish (Teleostei: Sisoridae) from Nepal and China.. 764 records from BioGIS - Fish - INPA database. 3108 records from SMNS Palaeontological collection - Fossil fishes and marine reptiles. 4 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 102895 records from Field Museum of Natural History (Zoology) Fish Collection. 37 records from A brief review of Triplophysa (Cypriniformes: Balitoridae) species from the Tarim Basin in Xinjiang, China, with description of a new species.. 6 records from Pseudogramma xanthum, a new replacement name for a serranid fish from the subtropical South Pacific Ocean with description of the species.. 6417 records from Norwegian Species Observation Service. 3 records from MSB Mammal Collection (Arctos). 519 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 748 records from MSB Host Collection (Arctos). 3762 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 14446 records from Trekvis - Migratory fishes in the river Scheldt. 142 records from Scottish Environment Protection Agency - Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 246852 records from Royal Netherlands Institute for Sea Research (NIOZ) - Kom Fyke Mokbaai. 3 records from Pseudojuloides zeus, a new deep-reef wrasse (Perciformes: Labridae) from Micronesia in the western Pacific Ocean. 52542 records from Inventaire National du Patrimoine Naturel : Atlas des poissons d'eau douce de France métropolitaine (2011). 4 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 8974 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 48082 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 190 records from Apteronotus caudimaculosus n. sp. (Gymnotiformes: Apteronotidae), a sexually dimorphic black ghost knifefish from the Pantanal, Western Brazil, with a note on the monophyly of the A. albifrons species complex.. 65 records from Collections ichtyologiques et herpétologiques (BOUM). 29 records from Wildlife Sightings. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 109 records from Countryside Council for Wales - Lamprey Survey Data. 23968 records from The Fish Database of Taiwan. 7 records from Animal Sound Archive. 4 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 18175 records from Oregon State Ichthyology Collection. 31 records from Description of Cathorops mapale, a new species of sea catfish (Siluriformes: Ariidae) from the Colombian Caribbean, based on morphological and mitochondrial evidence.. 300 records from A systematic revision of the genus Archocentrus (Perciformes: Cichlidae), with the description of two new genera and six new species.. 39892 records from Bernice P. Bishop Museum. 33 records from Pond Conservation - National Pond Monitoring Network collated pond survey data for Great Britain 1972 to 2007. 18 records from National Invasive Species Database. 1 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4060 records from Colección Ictiológica de la Universidad de Antioquia. 1 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar1. 2 records from Neobythitoides serratus, a new bathyal genus and species from the East China Sea (Teleostei, Ophidiidae).. 5 records from Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay.. 26 records from Akysis pulvinatus, a new species of catfish (Siluriformes: Akysidae) from southern Thailand.. 65 records from Sternarchorhynchus curumim (Gymnotiformes: Apteronotidae), a new species of tube-snouted ghost electric knifefish from the lowland Amazon basin, Brazil.. 14 records from Sparisoma tuiupiranga, a new species of parrotfish (Perciformes: Labroidei: Scaridae) from Brazil, with comments on the evolution of the genus.. 124 records from Staffordshire Ecological Record - SER Species-based Surveys. 9 records from UTEP Vertebrates. 1 records from ECatSym: Electronic World Catalog of Symphyta. 354 records from Condon Fossil Collection. 4 records from Pseudancistrus sidereus, a new species from southern Venezuela (Siluriformes: Loricariidae) with a redescription of Pseudancistrus.. 1 records from CU Invertebrate Paleontology. 31 records from A revision of the gobiid fish genus Trypauchen (Gobiidae: Amblyopinae).. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 3 records from Botany (UPS). 3 records from A new species of sponge-dwelling Elacatinus (Pisces: Gobiidae) from the western Caribbean.. 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Platyhelminthes. 1847 records from European Molecular Biology Laboratory Australian Mirror. 49157 records from NRM-Fishes. 91 records from Yorkshire Naturalists' Union Marine and Coastal Section - Yorkshire Naturalists Union Marine and Coastal Section Records. 26 records from Akysis longifilis, a new species of catfish (Teleostei: Akysidae) from Myanmar.. 75 records from Estonian Nature Observations Database. 2 records from Gymnotus ardilai: a new species of Neotropical electric fish (Ostariophysi: Gymnotidae) from the Rio Magdalena Basin of Colombia.. 464 records from Bocachico Prochilodus magdalenae (Characiformes: Prochilodontidae) en la cuenca media y baja del río Magdalena. 1396 records from National Taiwan Museum. 3 records from Ájtte. 894 records from Coleção de Ictiologia do Museu de Ciências Naturais do Centro Universitário Univates (ZIUMCN-UNIVATES). 2 records from Coryphopterus kuna, a new goby (Perciformes: Gobiidae: Gobiinae) from the western Caribbean, with the identification of the late larval stage and an estimate of the pelagic larval duration.. 66 records from The Neotropical annual killifish genus Pterolebias Garman (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology, and taxonomic revision.. 2 records from SMNS Palaeontological collection - Cretaceous and jurasic invertebrates. 33 records from Astyanax endy (Characiformes: Characidae), a new fish species from the upper Río Bermejo basin, northwestern Argentina.. 1133 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 6827 records from Colección de peces y macroinvertebrados del Museo de Historia Natural de la Pontificia Universidad Javeriana. 208717 records from Fish (NSMK-PI). 9334 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN.. 4 records from Two new species of the genus Chlopsis (Teleostei: Anguilliformes: Chlopsidae) from the Southwestern Pacific.. 594 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 1076 records from Fishes of the Congo River 2010 Expedition. 34 records from Revision of the Bahamian cave-fishes of the genus Lucifuga (Ophidiiformes, Bythitidae), with description of a new species from islands on the Little Bahama Bank.. 3 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 44721 records from Marine Conservation Society - Seasearch Marine Surveys. 13 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 57 records from A new Stomatorhinus (Osteoglossomorpha: Mormyridae) from the Ivindo River, Gabon, West Central Africa.. 28 records from A new species of the freshwater fish genus Astyanax (Ostariophysi: Characidae) from the rio Iguacu basin, southeastern Brazil.. 9 records from Countryside Council for Wales - Freshwater Site Visits. 8 records from Scarus maculipinna, a new species of parrotfish (Perciformes, Scaridae) from the eastern Indian Ocean.. 2457 records from Colección de Ictiología. 2044 records from Queen Victoria Museum Art Gallery provider for OZCAM. 25 records from Lethrinus ravus, a new species of emperor fish (Perciformes: Lethrinidae) from the western Pacific and eastern Indian oceans.. 27 records from A new species of Astyanax (Teleostei, Characiformes, Characidae), with breeding tubercles, from the Paraná and Uruguay river basins.. 9 records from Rivulus uakti sp. n. and R. amanapira sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new species from the upper Rio Negro, Brazilian Amazon.. 1722 records from Census of fishes in watercourses in Benin. 164 records from Données ONF Faune-Flore-FOnge. 35 records from Neoniphon pencei, a new species of holocentrid (Teleostei: Beryciformes) from Rarotonga, Cook Islands. 1 records from Collection Paleoanthropology SMF. 36 records from Pseudolaguvia ferula, a new species of sisoroid catfish (Teleostei: Erethistidae) from India.. 49 records from New species of the amphiliid catfish genera Amphilius, Doumea and Phractura and the taxonomy of Paramphilius from West Central Africa (Siluriformes, Amphiliidae).. 1 records from AUM Fish Collection. 277 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 184 records from National System of Protected Areas in Poland - Animals. 36 records from Ecsenius caeruliventris and E. shirleyae, two new species of blenniid fishes from Indonesia, and new distribution records for other species of Ecsenius.. 236032 records from United States Geological Survey Nonindigenous Aquatic Species Database. 27 records from A new species of the gobiid fish Trimma from the Western Pacific and Northern Indian Ocean coral reefs, with a description of its osteology.. 7 records from Micralestes (Characiformes, Alestidae) of the lower Congo River, with a description of a new species endemic to the lower Congo River rapids in the Democratic Republic of Congo.. 4376 records from MfN - Fossil Fish Collection. 49 records from Acanthopagrus taiwanensis, a new sparid fish (Perciformes), with comparisons to Acanthopagrus berda (Forsskål, 1775) and other nominal species of Acanthopagrus.. 43 records from Notes on the snake eels of the genera Apterichtus and Ichthyapus (Anguilliformes: Ophichthidae) of the Central and South Pacific, with the description of a new species.. 2410 records from Centre for Environmental Data and Recording - Marine Data from Northern Ireland. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 1614 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 731 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 155200 records from Australian Museum provider for OZCAM. 10 records from Two new species of eelpouts (Teleostei, Zoarcidae) of the genus Seleniolycus from the Ross Dependency, Antarctica.. 239 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 16 records from A review of the gobiid genus Akko (Teleostei: Gobiidae) with description of a new species.. 2490 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 1 records from SMNS Palaeontological collection - Invertebrates (Palaeozoic, Mesozoic). 316 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 6 records from National Trust - Heigham Holmes species data held by The National Trust. 152 records from BioFresh Pond Data. 18 records from Two new fish species of the genus Puntius Hamilton (Cyprinidae) from Manipur, India, with notes on P. ticto (Hamilton) and P. stoliczkanus (Day).. 48 records from A new species of Psilorhynchus (Teleostei: Psilorhynchidae) from the Ataran River Basin, Myanmar, with comments on the generic name Psilorhynchoides.. 7 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 2005 records from Scottish Natural Heritage - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by Scottish Natural Heritage. 22 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 7 records from Microcambeva ribeirae sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new sarcoglanidine catfish from the Rio Ribeira do Iguape basin, southeastern Brazil.. 3 records from Trichomycterus santanderensis: A new species of troglomorphic catfish (Siluriformes, Trichomycteridae) from Colombia.. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 7718 records from Occurrences in SinBIOTA. 2 records from Gymnothorax hansi, a new species of moray eel (Teleostei: Anguilliformes: Muraenidae) from the Comoro Islands, Western Indian Ocean.. 5 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 48 records from Paleontological collection of the National Museum - Flora. 2567 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 4535 records from Anymals+plants - Citizen Science Data. 247 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 31 records from Baekdu Mountain Animal. 91497 records from UAIC Ichthyological Collection. 4547 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 56 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 5632 records from Invasive species - American bullfrog (Lithobates catesbeianus) in Flanders, Belgium. 12 records from Clarias insolitus, a new species of clariid catfish (Teleostei: Siluriformes) from southern Borneo.. 1571 records from Colección Ictiológica de la Universidad Industrial de Santander. 1 records from SMNS Palaeontological collection - Fossil amphibes and terrestrian reptiles. 6 records from Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea.. 6602 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter. 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 1 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 216949 records from UF FLMNH Ichthyology. 8439 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 3254 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 4 records from Simpsonichthys nielseni sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the São Francisco River basin, Brazil.. 74 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 4 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 179 records from Seven new species of the Neotropical electric fish Gymnotus (Teleostei, Gymnotiformes) with a redescription of G. carapo (Linnaeus).. 7 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 9023 records from Fish collection, Natural History Museum, University of Oslo. 6 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 3413 records from Taiwan Fisheries Research Institute – Digital archives of coastal and offshore specimens. 42 records from Pseudecheneis suppaetula, a new species of glyptosternine catfish (Teleostei: Sisoridae) from India.. 665 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 33 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 86 records from Paleontological collection of the National Museum - Fauna. 238 records from Collection Pisces - KAUMM. 22 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 19 records from Three new species of Microbrotula (Teleostei: Ophidiiformes: Bythitidae) from the Indo-West Pacific.. 120950 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7301 records from Ichthyology. 33 records from The identity of Pseudomystus moeschii (Boulenger, 1890), with the description of two new species of bagrid catfishes from Southeast Asia (Teleostei: Bagridae).. 814 records from Fish monitoring data in Lake Kasumigaura. 16 records from Collection Paleontology - GPIT. 6 records from Synodontis acanthoperca, a new species from the Ogooue River system, Gabon with comments on spiny ornamentation and sexual dimorphism in mochokid catfishes (Siluriformes: Mochokidae).. 1162 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 15 records from A new species of Cynopotamus Valenciennes, 1849 (Characiformes, Characidae) with a key to the species of the genus.. 58 records from European Seabirds at Sea (ESAS) bird sightings from 1980 to 2003.. 3208 records from A dataset from bottom trawl survey around Taiwan. 21465 records from South Australian Museum Australia provider for OZCAM. 1624 records from National Museum of Natural Science. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 9895 records from Freshwater fishes of the Western Balkans. 15495 records from observe_tuna_ecoscope. 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 3 records from Bird Collection of Museum and Institute of Zoology PAS. 255 records from Countryside Council for Wales - Bullhead Survey Data in Wales. 6 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2234 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups.
Keywords: GBIF; biodiversity; species occurrences